SAFETY KNOWLEDGE – A SYSTEMATIC LITERATURE REVIEW - Nur Shazliaida Shaidan; Muhammad Asyraf Mohd Kassim; Ummi Naiemah Saraih; Mohd Fitri Mansor; Muhammad Safizal Abdullah; Wan Mashumi Wan Mustafa (Journal of Human Development and Communication (JoHDeC), 2025)
Safety is an imperative element within organisations, including the manufacturing industry in Malaysia, and prioritising safety knowledge is essential for establishing a secure working environment. This paper provides a comprehensive review of current research on safety knowledge, specifically focusing on the influential factors, given that this predictor has received serious attention in the occupational safety literature in manufacturing organisations. The review discusses the concept of safety knowledge, factors influencing safety knowledge and gaps in the literature in previous studies. The final section of the paper offers a discussion on potential avenues for future research and concludes with insights pertinent to this study’s findings.